Let $a(n,t)= \sum_{k=0}^n \binom{n}{k}^2t^k.$

Using generating functions it is easy to show that

$$\sum_{k=0}^n a(k,t) a(n-k,t)=1/2 \sum_{k=0}^n \binom{2n+2}{2k+1}t^k.$$

Is there also a combinatorial proof of this identity?

For $t=1$ this reduces to $\sum_{k=0}^n \binom{2k}{k}\binom{2(n-k)}{n-k}=2^{2n}$, for which various combinatorial proofs are known.


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Browse other questions tagged or ask your own question.